THE INTERACTION EFFECT OF TECHNOLOGY UTILIZATION TOWARD PROJECT PERFORMANCE: A HIERARCHICAL REGRESSION ANALYSIS - Hafnidar Abdul Rani; Che Sobry Abdullah; Shahimi Mohtar (JURNAL TEKNIK SIPIL, 2012)
Abstract: This study investigates the moderating effects of technology utilization toward project performance. Hierarchical regression analysis was utilized for hypotheses testing. The result of the hierarchical regression analysis showed support for some of the moderating effects. Analysis results as a whole appears that technology utilization as a moderator the relationship between the project management function and project performance. The study was not limited to the construction company that has a specific class qualification, but including all of the grade 2 to grade 7. The outcome of this study provides vital information and also provides an insight into further understanding on the issue of interface on the effect of technology utilization toward project performance in Aceh construction organizations.Keywords : project management, project performance, technology utilization, hierarchical regression analysis.Abstrak: Penyelidikan ini mengkaji efek penengah dari pemanfaatan teknologi terhadap kinerja proyek. Analisis regresi hirarki yang digunakan untuk menguji hipotesis. Hasil analisis regresi hirarki menunjukkan dukungan untuk beberapa efek penengah. Hasil analisis secara keseluruhan ditemui bahawa pemanfaatan teknologi sebagai penengah hubungan antara fungsi manajemen proyek dan kinerja proyek. Penyelidikan ini tidak terbatas pada perusahaan konstruksi yang memiliki kualifikasi kelas tertentu, melainkan termasuk semua kelas 2 sampai dengan kelas 7. Hasil kajian ini memberikan informasi penting dan juga memberikan wawasan dalam pemahaman yang lebih lanjut mengenai isu tentang efek pemanfaatan teknologi terhadap kinerja proyek dalam organisasi konstruksi di Aceh.Kata kunci : manajemen proyek, kinerja proyek, pemanfaatan teknologi, analisis regresi hirarki.